DESIGN OF FLEXIBLE PAVEMENT WITH COMPONENT ANALYSIS METHOD ON THE TUMATANGTANG-PANGOLOMBIAN ROAD SEGMENT OF TOMOHON CITY - Siska Masse; Toar Pangkey; N. Mamarimbing Mamarimbing; Titof Tulaka (Pendidikan Teknik Mesin, 2022)
Roads are an important infrastructure in the completeness of an area to support human needs. The plan to open a Paragliding tourist attraction, precisely in Kentur Toulangkow, requires adequate transportation facilities. The Tumatangtang Pangolombian road section will later become the access road to the place and will make it easier to connect between Pangolombian Village to Tumatangtang. Thus, good road planning is needed, especially regarding the thickness of the flexible pavement layer. This study aims to determine how thick the pavement layer is needed on the road. The method used in planning this time is the Component Analysis Method, namely by paying attention to factors such as traffic loads, environmental factors, and also the strength of the subgrade. From the calculation and discussion of the Tumatangtang-Pangolombian road section with a road length of 1.6 km and a width of 7 m with CBR 4.25% subgrade, 13.63% traffic growth, and a design life of 10 years, the required thickness of flexible pavement is obtained. namely 8 cm Laston (MS 744) for the surface layer, 18 cm of Class A Crushed Stone (CBR 100%) for the top foundation layer, and 25 cm of Sirtu/Pytrun Class A (CBR 70%) for the Sub foundation layer. Keywords: Pavement Thickness, Flexible Pavement, Component Analysis Method.